Novos horizontes no ensino de História: desafios, tecnologias e a criação de um MOOC - Dorneles Junior, Eldo (2024)
This dissertation explores the integration of Digital Information and Communication Technologies (TDICs) in the teaching of History, aligning with the guidelines of the National Common Curricular Base (BNCC). The general objective is to develop and evaluate pedagogical strategies that employ TDICs to promote critical and engaging learning, confronting manifestations of negationism and historical revisionism. The dissertation addresses the evolution of history teaching in Brazil, the influence of TDICs on students' daily lives, and proposes strategies for integrating these technologies in a critical and reflective manner. It includes the creation of an open online course (MOOC) as part of the ProfHistória program, offering a comprehensive view of the effective integration of TDICs in history teaching. The research reflects on the need for adaptable teaching methods and how TDICs can be used to enrich pedagogical practices, promoting a more interactive and collaborative educational environment. The study highlights the importance of an educational model that is reflective and adaptive, capable of responding to constant changes in the educational and technological landscape. The dissertation invites a continuation in the pursuit of improving the teaching of History, integrating digital technologies critically and consciously, aiming for a meaningful, inclusive, and transformative education.The MOOC, a product of this dissertation, stands out in an innovative educational context, showcasing how digital technologies can transform history teaching. By demonstrating the effectiveness of modern educational methods and the importance of making historical learning accessible and high-quality, this MOOC moves towards a more inclusive and impactful history education, leveraging digital technologies to enrich the learning experience.